(untitled) (Journal of Hama University, 2024)
The cement industry is like the fertilizer industry and for long periods it is classified among the intentionally polluted industries through its gaseous pollutants, dust, solid waste and polluted water. However, scientific progress has successively created solutions to control these pollutants so that these industries achieve the global standards necessary for mourning in them and ensuring the achievement of development. The compost plant is not new historically, as the phosphogym produced by the compost production process is used, but what is new in our research is the use of a fermented compost plant. Hence the importance of the research by highlighting a new idea that focuses on finding environmentally appropriate ways to get rid of this type of industrial waste, which contributes to protecting the environment. An adjunct to pozzolana, to ensure that the product meets the standard specification for Ordinary Portland Cement No. 3411 for the year 2008.This proposed solution achieves many environmental and economic benefits, the most important of which are: 1- the disposal of huge quantities of phosphodiester in the open barefoot, 2-considerng phosphogypsum as a good addition material, as it will reduce cement costs on the one hand, 3- preserving the natural resources represented by the pozzolan quarries in the As-Suwayda Governorate. 4-economic gains, the most important of which is reducing the cost of cement production by reducing transport wages.